Homeschooling: An alternative to mainstream - Yin, LC; Zakaria, A; Baharun, H (CRC Press-Taylor & Francis Group, 2024)
Homeschooling is a parent-led home based education, which is currently enjoying new-discovered acceptance both locally and internationally. To understand this new alternative education, we review a number of homeschooling studies from the local and overseas associated with the history and development of homeschooling, factors that led to homeschooling; outcome or impacts of homeschooling on school, families and children, and concerns, challenges as well as critics of homeschooling. We then document the findings of reasons that led to homeschooling and its outcomes to give an overview of homeschooling to provide a guideline and reflection to parents who intend to homeschool their children. Also, it is significant for the current conventional education system to re-attract families who chose homeschool as well as to refine the current educational practice to cater the modern generation. Meanwhile, we also document concerns, challenges, and critics towards homeschooling to ameliorate homeschooling as the growing alternative.